EMBR-05. TUMORS OF THE PINEAL REGION CAN BE CLASSIFIED INTO DISTINCT SUBGROUPS BASED ON MOLECULAR CHARACTERISTICS CORRELATING WITH CLINICAL PARAMETERS AND GENETIC ALTERATIONS. Issue 2 (22nd June 2018) - Pfaff, Elke; Snuderl, Matija; Karajannis, Matthias A; Aichmüller, Christian; Sill, Martin; Orr, Brent A; Ellison, David W; Pfister, Stefan M; Jones, David T W
Abstract: Several different entities with distinct clinical and histopathological features are described within in the group of pineal tumors. Whereas pineocytoma (PC), pineal parenchymal tumors of intermediate differentiation (PPTID) and papillary tumors of the pineal region (PTPR) predominantly affect adults and are associated with a relatively favorable prognosis, pineoblastoma (PB) occurs at young age and constitutes a highly aggressive tumor. Despite multimodal treatment, prognosis is poor (especially for infants and patients with metastatic disease), and therapeutically actionable molecular targets are lacking to date. Most PB arise sporadically, however, DICER1 or RB1 germline mutations are known to predispose to the development of PB, the latter in the context of trilateral retinoblastoma. Genome-wide DNA methylation profiling and copy-number analysis were used to investigate the biological features of 230 pineal tumors of different histologies. Known histopathological entities (PC, PTPR, PPTID) could be clearly separated by unsupervised clustering, as well as further distinct subgroups, including the previously hypothesized PTPR-A and PTPR-B groups. Notably, several biologically discrete subgroups were formed by the tumors initially diagnosed as PB or pineal primitive embryonal tumors/PNETs, which showed distinct clinical associations (e.g. age distribution). Somatic deletions of DROSHA, an endoribonuclease involved in miRNA processing upstream of DICER1, seem to be a recurrent feature of the largest subgroup. Rarer DICER1 and DGCR8 alterations in this group confirm a central role of altered miRNA biogenesis in the development of this subset of PB. Further molecular and functional characterization of novel sub-clusters, including ongoing miRNA-seq, will provide insights into the oncogenesis of PB.